THE DEVELOPMENT OF COMMUNICATION SKILLS OF STUDENTS OF SECONDARY SCHOOL AS A COMPONENT OF THEIR LEADERSHIP POTENTIAL - Kovalchuk, Vasyl; Yermak, Tatiana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The professional effectiveness depends on many factors, and good verbal communication skills, as a basis for productive relationships, mutual understanding and realization of goals and objectives of professional effectiveness as a way of self-improvement, self-realization and overcoming personal crises, are of great importance. The communication skills are basic ones in forming a leader. The concept of "communication skills" in the article is defined as the ability to communicate effectively, the ability to understand what the interlocutor means and be understood by them, the ability to negotiate, achieve their goals through communication. This type of skills performs many important functions in the personal development: provides psychological comfort, allows you to organize joint activities, meets the natural human need for communication, helps to assert itself, socially realize themselves. The success of a person in life depends on the ability to communicate. The personal success depends on the communication skills. Communication skills are important both for the social realization of the individual and for psychological life satisfaction. The article substantiates the problem of developing students' communication skills. The pedagogical conditions for the development of students' communication skills, including: creation of a favorable educational environment, application of a personality-oriented approach to learning, modeling of real professional communication conditions, are identified and substantiated. Information-communicative, regulatory-communicative and affective-communicative skills are singled out. To determine the level of development of these skills, we used the method of determining communicative levels of communicative and organizational tendencies: very low, low, medium, high. The study involved 196 students and 30 teachers of the educational complex of lyceum №157 in Kyiv.